Low level of pre-vaccination measles antibody among infants receiving measles immunization in ilorin, Kwara state, Nigeria (2013)
This study was designed to assess the low levels of pre-vaccination measles antibody among infants receiving measles immunization in Ilorin, Kwara State, Nigeria. Pre-vaccination blood samples were obtained from 400 infants brought to the EPI Clinic of the University of Ilorin Teaching Hospital, Ilorin, Nigeria. Blood samples were collected by finger puncture onto ROPACO (Rochester, USA) rectangular filter paper measuring 7 cm by 10 cm. Other information like name, age, sex, date of vaccination was also recorded on the filter paper. The filter papers were dried at ambient temperature and stored in plastic bags at -20℃ until ready for serum extraction. Specimens were analyzed for measles antibody using Hemagglutination Inhibition technique. Data generated were subjected to Chi square statistical test to establish association between categorical variables with dichotomous outcomes. Of all the 400 infants screened for pre-vaccination measles antibodies, 29(7.2%) had protective antibody titer while 156 (39.0%) had low titer since ≥40 HI titer is the study threshold of protection against measles while 215(53.8%) had no detectable measles antibody titer (<1:10). Thirty-one (8.0%) of the infants had measles prior to vaccination. Previous history of measles was significant associated (P=0.0005, X2 = 34.507) with the level of pre-vaccination measles virus antibody. There was no significant difference (p=0.723) in the level of measles virus antibody among the exclusively breastfed infants and those that were not exclusively breast fed. Age (p=0.839) and sex (p=0.1999) were not significantly associated with the level of measles virus antibody. The distribution of this antibody levels appeared stable with no significant difference between age groups, sex and breast feeding pattern. Only the previous history of measles showed statistical association with measles virus antibody proportion. In conclusion, a larger proportion (53.8%) of the children had no detectable anti-measles virus antibody while 39.0% had low (non-protective) titer; these put both groups at risk of developing measles given the endemic nature of Nigeria. Therefore, re-evaluation of 9 months as the age for measles vaccination in Nigeria vis-à-vis 92.8% with <40 HI titer is highly recommended.